(untitled) (Kinesiology, 2022)
Physical education curricula in Polish schools should include more tasks to increase physical activity. The Tabata Training Program can help regulate body weight and induce changes in body fat and physical fitness. This study aimed to determine the effects of a 10-week PE curriculum supplemented by a Tabata Training Program on health-related fitness in 16-year-old secondary school students. The study examined 187 students (66 boys and 121 girls) assigned to either a Tabata Training Program intervention or control group. The intervention lasted 14 minutes during one physical education lesson per week. Pre- and post-intervention, anthropometric measurements were taken, and each participant performed physical fitness tests to evaluate muscular strength, flexibility, speed/agility, and cardiovascular efficiency. Boys of the intervention group significantly reduced body fat (by 1.77%, p<.05) and increased cardiovascular efficiency (the physical efficiency index was higher by 3.61 points, p<.05). Girls increased cardiovascular efficiency only (the physical efficiency index increased by 5 points, p<.001). However, slight changes in motor parameters were observed in all the participants. The Tabata Training Program demonstrated partial effectiveness but should be individualized and sex differences should be considered. Key words: physical education, intervention study, exercise training, youth